Syllabus Design for PKN-STAN Entrance Test: A Need Analysis - Muhammad Hasan Basri (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The aim of this study is to scrutinize the needs of the prospective students of Politeknik Keuangan Negara – Sekolah Tinggi Akuntansi Negara (PKN-STAN) as well as to design syllabus for preparation program of PKN-STAN entrance test. This research was a descriptive research in which questionnaires were distributed to prospective students and on-going students of PKN- STAN while interviews were administered to graduates of PKN-STAN, English teachers of senior high school and English lecture. To obtain more accurate information on prospective students’ needs. The data were analysed in quantitative and qualitative method. The findings of this study revealed the needs for setting up the syllabus for preparation program of PKN-STAN entrance test. The proposed syllabus provided a set of topics/ materials on structure and written expressions and reading comprehension. The syllabus was implemented to prototype course materials completed with exercises. The syllabus was an integration of aims, objectives, and activities to bridge the gap on the prospective students’ present knowledge and the required knowledge for PKN-STAN entrance test..